Assessment of low amounts of meat and bone meal in the diet of laying hens by using stable isotopes - Madeira, Luciene Aparecida [UNESP]; Denadai, Juliana Celia [UNESP]; Ducatti, Carlos [UNESP]; Pezzato, Antonio Celso [UNESP]; Araujo, Priscila Cavalca de [UNESP]; Pereira Sartori, Maria Marcia [UNESP]; Pizzolante, Carla Cachoni; Sartori, Jose Roberto [UNESP] (Univ Estadual Londrina, 2015)
The aim of this study was to assess whether the inclusion of low amounts of ingredients such as wheat bran, corn gluten and yeast in the diet of laying hens can interfere with the traceability of meat and bone meal (MBM) in eggs and its fractions (albumen and yolk). We used 256 laying hens distributed across eight treatment groups, which consisted of a diet based on corn-soybean-wheat (CSW) bran meal and other diets that had additions comprising gluten and/or (MBM) and/or yeast. To analyse the isotopic ratios (C-13: C-12 and N-15:N-14), on the 28th and 56th days, 16 eggs were randomly taken for each treatment (four for each repetition), where eight eggs (two for each repetition) were used to harvest yolk and albumen samples and the remaining eight (two for each repetition) were used to analyse the whole egg. We concluded that detection of 2.0% MBM in the egg and its fractions is possible; however, the results for treatments containing gluten and yeast were not different from those containing MBM. Therefore, the inclusion of 3.0% gluten and/or yeast does not result in different delta C-13 and delta N-15 isotopic values in the egg and its fractions compared to the values obtained with the addition of 2.0% MBM in the diet.

"O objetivo foi verificar se a baixa inclusão de outros ingredientes, como farelo de trigo, glúten de milho e levedura na dieta de poedeiras, pode interferir na rastreabilidade da farinha de carne e ossos bovinos (FCOB) em ovos e suas frações (albúmen e gema). Foram utilizadas 256 galinhas poedeiras distribuídas em oito tratamentos, no qual, foram compostos de uma dieta MST a base de milho, farelo de soja e farelo de trigo e as demais dietas foram acrescidos de glúten e/ou (FCOB) e/ou levedura. Para análise da razão isotópica (13C/12C e 15N/14N), nos 28º e 56º dias foram tomados aleatoriamente 16 ovos por tratamento (quatro por repetição), onde oito ovos (dois por repetição) serviram para colheitas de amostras de gema e albúmen e os outros oito (dois por repetição) para ovo total. Pode-se concluir que, a detecção de 2,0% de FCOB no ovo e suas frações é possível, porém, os tratamentos com inclusão de glúten e levedura não foram diferentes dos tratamentos com inclusão da FCOB. Portanto, a inclusão de 3,0% de glúten e ou levedura na ração, não permite a diferenciação dos valores isotópicos de δ13C e δ15N do ovo e suas frações destes grupos dos que possuem 2,0% FCOB."
Determinação de baixa inclusão de FCOB em dietas de poedeiras por isótopos estáveis
Keywords: Carbon-13; Corn gluten; Yeast; Nitrogen-15; Carbono-13; Glúten de milho; Levedura; Nitrogênio-15